A mathematical model for processes of structure analysis - Vásárhelyi, Anna (Computer Assisted Methods in Engineering and Science, 2023)
Generally, path-following algorithms are used for the history analysis of structures. Now, a new approach is presented for solving the problem by parametric optimization. The optimization problem is solved in a direct product of function spaces. The necessary conditions of the stationarity of a curve are examined. A method is presented for determining a piece of a continuous component of the Karush-Kuhn-Tucker stationary curve depending on one parameter which transforms the problem into the space l2 .